Peran Sistem Imun dan Hematologi dalam Menghadapi Infeksi Covid-19 - Azizah Nabhila; Sovie Hidayatun N; Revalina Aulia R; Aurel Tata L; Salwa Ramadanni; Shonza Affina S; Liss Dyah Dewi Arini (Journal of Literature Review, 2025)
The COVID-19 pandemic is a serious global threat, affecting more than 200 countries. Indonesia is among the hardest-hit countries, with a mortality rate of 8.9% in March 2020. Preventive measures are needed to suppress the spread of this disease. Therefore, effective response strategies must be implemented immediately to mitigate the impact of this pandemic. These strategies include increasing public awareness, implementing health protocols, and increasing healthcare service capacity. Furthermore, further research on COVID-19 is needed to understand the characteristics and dynamics of its spread. This will hopefully suppress the spread of COVID-19 and prevent disruptions to people's quality of life. The government and the public must work together to overcome this pandemic.